Early Platelet-Collagen Interactions in Whole Blood and Their Modifications by Aspirin and Dipyridamole Evaluated by a New Method (Basic Wave) - Pérez-Requejo, José Luís; Aznar, Justo; Santos, M Teresa; Vallés, Juana (Thrombosis and Haemostasis, 1985)
It is shown that the supernatant of unstirred whole blood at 37° C, stimulated by 1 μg/ml of collagen for 10 sec, produces a rapid generation of pro and antiaggregatory compounds with a final proaggregatory activity which can be detected for more than 60 min on a platelet rich plasma (PRP) by turbidometric aggregometry. A reversible aggregation wave that we have called BASIC wave (for Blood Aggregation Stimulatory and Inhibitory Compounds) is recorded. The collagen stimulation of unstirred PRP produces a similar but smaller BASIC wave. BASIC’s intensity increases if erythrocytes are added to PRP but decreases if white blood cells are added instead. Aspirin abolishes “ex vivo” the ability of whole blood and PRP to generate BASIC waves and dipyridamole “in vitro” significantly reduces BASIC’s intensity in whole blood in every tested sample, but shows little effect in PRP.
Keywords: BASIC wave; Platelet-collagen interactions; Whole blood; Dipyridamole; Aspirin